Memorial Sites in St. Innokenty’s homeland - Chertilov, Alexei (project baikal, 2022)
The article is devoted to the cultural heritage sites of memorial importance, which are included in the complex of the Cultural and Educational Center named after St. Innokenty Veniaminov opened in 2017 in his homeland, the Verkholensk village of Anga: the hut where he spent his childhood, and the foundations of the lost Church of the Prophet Elijah, in which he helped his uncle deacon in his divine service.
Keywords: Anga; Lena River; Saint Innokenty Veniaminov; Church of the Prophet Elijah; piece of folk wooden architecture; cultural heritage; architectural and archaeological excavations